THE IMPLEMANTATION OF PRUDENTIAL PRINCIPLE TOWARDS PD BPR BANK SLEMAN IN THE EFFORT OF PREVENTING NON PERFORMING LOANS FOR UMKM CREDIT CUSTOMERS IN SLEMAN REGENCY - Desi Eka Permatasari; Sudiyana Sudiyana; Paryadi Paryadi (Kajian Hasil Penelitian Hukum, 2018)
The main function of banking Indonesia as collectors and distributors of public funds. According to Article 2 of Low number 10 of 1998 about banking, PD BPR Bank Sleman is obliged to implement prudential principle in preventing non performing loans for UMKM credit customers. The formulation of the problem in this research is how does PD BPR bank Sleman implement prudential principle in giving credit UMKM to its customers. This research is normative legal research. The type of the research used is the normative juridical research so that the legislation used is the approach of legislation with the source data in the form of primary, secondary, and tertiary legal material. Data collecting technique is done by literature study technique which study material of law and analyzed by using descriptive qualitative analysis. Form the results of the study, it can be concluded that PD BPR Bank Sleman has applied prudential principle as set forth in article 2 of law number 10 year 1998. The effort has been done by PD BPR Bank Sleman in preventing of non performing loans for UMKM is by giving additional policy of collateral as much as 30 persen which must be borne by the debtor. This is doneby PD BPR Bank Sleman as a form of caution, because the government only bear 70 persen, while 30 persen must be borne by the bank PD BPR Bank Sleman. The efforts which are made by PD BPR Bank Sleman to overcome this problem is done by 2 ways, namely by making continuous billing in a persuasive with kinship and by tightening credit analysis to the business owned by prospective borrowers.